Particular features of the clinical course of the papilloma viral infection depending on quantitative indices of human papilloma viruses of a high carcinogenic risk - M. R. Rakhmatulina; N. V. Bolshenko; D. A. Kuevda; O. B. Trofimova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal of the study. To study the dependence of the clinical course of the papilloma viral infection and cytological characteristics of lesions in the cervical mucosa on the quantitative indices of human papilloma virus (HPV). Materials and methods. The study involved 175 female patients with HPV of a high carcinogenic risk including 125 subjects with clinical forms of the papilloma viral infection (PVI) and 50 subjects with subclinical and latent forms of the disease. Laboratory tests were carried out with the use of the polymerase chain reaction including real-time PCR for the quantitative determination of HPV. Cytological examinations of scrapes from the exocervical and endocervical mucosa were carried out according to Leishman I, and the results were interpreted according to Bethesda. Results. The authors established an association between clinical forms of PVI and infection with two or more HPV genotypes, and latent and subclinical forms of the disease and infection with one HPV genotype; HPV Genotype 16 prevails within the structure of HPV of a high carcinogenic risk. It was shown that patients infected with two or more HPV genotypes as well as subjects with subclinical and latent forms of the disease underwent reliably higher viral loads than subjects with anogenital warts and patients infected with one HPV genotype only. A higher HPV viral load was also noted in case of a persisting course of PVI and in patients with high-grade squamous intraepithelial lesions (H-SIL). Conclusion. Women with latent and subclinical forms, persistent PVI course and infected with two or more HPV genotypes of a high carcinogenic risk belong to the high-risk group developing expressed epithelial affections in the cervical mucosa. Quantitative HPV indices exceeding 5 lg of copies of HPV DNA per 100,000 cells belong to unfavorable predictors for the development of intraepithelial affections in the cervical mucosa and stipulate the need to conduct an additional examination (colposcopy or cytology) to exclude their development.